Implementation of Detachable Reversible Data Hiding in Image Encryption - Pradeep, Musham; Srilatha, D (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper proposes a scheme for detachable reversible data hiding in image encryption. In which the sender encrypts an image using encryption key. Then, the data is appended to the encrypted image using a data-hiding key. With an encrypted image containing additional data, if a receiver has the data-hiding key, he can extract the additional data though he does not know the content of the image. If the receiver has the encryption key, he can decrypt the encrypted image and get an image similar to the original one, but he cannot extract the additional data. If the receiver has both the data-hiding key and the encryption key, he can extract the additional data and recover the original image without any error.